(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
This article examines investment activity in the construction materials industry, focusing on current trends and key structural changes under modern economic conditions. The study analyzes the dynamics of investment flows, identifies the main factors influencing investment attractiveness, and evaluates the role of technological modernization, digitalization, and innovation in shaping investment processes within the sector. Particular attention is paid to the impact of macroeconomic factors, state support measures, and institutional conditions on investment decision-making in the construction materials industry. Based on analytical assessment, the article reveals existing challenges and constraints limiting investment growth, while also highlighting promising directions for enhancing investment efficiency and sustainability. The findings contribute to a deeper understanding of investment development trends in the construction materials industry and may serve as a practical basis for policymakers, industry stakeholders, and researchers in developing effective investment strategies.